Utility, Strategy, and Social Decision Rules: Comment - Tullock, Gordon (Quarterly Journal of Economics, 1961)
Journal Article Utility, Strategy, and Social Decision Rules: Comment Get access Gordon Tullock Gordon Tullock University of South Carolina Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 75, Issue 3, August 1961, Pages 493–496, https://doi.org/10.2307/1885135 Published: 01 August 1961